On the first South American records of widespread linyphiid spiders (Araneae) - Cajade, Manuel; Rodrigues, Everton N. L.; Hagopián, Damián; Laborda, Álvaro; Brescovit, Antonio; Simó, Miguel (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
The linyphiid species Agyneta galapagosensis (Baert, 1990), Erigone autumnalis Emerton, 1882 and Mermessus fradeorum (Berland, 1932) are recorded for the first time on the continental South America. In addition, the distribution data of Neriene redacta Chamberlin, 1925 is expanded. Figures of the habitus, a distribution map of the new records and new data about the natural history of these species are provided. These results show the high dispersal capacity and adaptability of these linyphiid spiders to different environmental conditions, such as agroecosystems and urban areas.